Regeneração natural após remoção de espécies vegetais exóticas invasoras em um fragmento da floresta ombrófila mista - Frasson, Marcia Lapa (2011)
The Conservation Areas are presented as an alternative to preservation and conservation of biodiversity, as they contribute to the maintenance of interactions in natural ecosystems. Contrary to this process, the advance of occupation of these areas by invasive alien species and the environmental impact they cause have been the keynote of the interest aroused in the survey to ensure environmental quality of the ecological point of view, creating mechanisms for environmental management to enable the restoration of native biodiversity and restoration of ecological processes. Natural Park Municipal Tanguá as part of Project BIOCITY the Department of the Environment in Curitiba, were removed in 2007, 381 individuals of Pinus and Eucalyptus. However, no monitoring of the regeneration of invasive alien species and their impact on the regeneration of native species of the fragment of the Rain Forest (Araucaria Forest). The aim of this study was to evaluate the structure of vegetation, as well as the impact of invasive alien species on the regeneration of native species. The study was conducted in the natural remainder were recorded live individuals of species that are regenerating naturally in two areas where there was the removal of invasive alien plant species, and the area in which there is recorded the presence of invasion (control area) called Regeneration 1 (R1), Regeneration 2 (R2) and Regeneration 3 (R3), respectively. The phytosociological parameters were estimated: density (absolute and relative), frequency (absolute and relative), dominance (absolute and relative), importance value, the rate of biodiversity and floristic similarity. The floristic survey results showed how the presence of 46 species from 37 genera and 24 families and the families Asteraceae, Fabaceae, Rosaceae, Solanaceae, the most representative. The species with highest importance values were 146.9 Allophylus edulis (R3), Baccharis dracunculifoia 54.3 (R1) and Myrsine coriacea 45, 9 (R2). The Shannon diversity index (H ') showed 1.82 in R1, R2 of 2.42 and 2.40 for R3. As for the similarity index of Jaccard demonstrates the ressultado little similarity, 4% between R1 and R2, 0% between R1 and R3, and 18% between R2 and R3. The forest fragment is greatly altered by human activities, however there is natural regeneration under conditions favorable for the presence of species of native flora in a succession process in comsiderado initial R1, R2 and R3 advanced intermediate. From the results obtained and conclusions, was presented a set of guidelines for environmental management of the Conservation Unit regarding the proper management of invasive alien plant species to be implanted in the conservation area.